2016
DOI: 10.1007/s13555-016-0122-9
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Efficacy of Thalidomide and Lenalidomide in the Treatment of Refractory Prurigo Nodularis

Abstract: Prurigo nodularis (PN) is a chronic dermatoses characterized by intensely pruritic, excoriated, or lichenified nodules. Standard therapy includes corticosteroids, antihistamines, and phototherapy; however, treatment results are often inadequate or transient. Thalidomide and its analogue lenalidomide are immunomodulatory drugs that have successfully been used to treat refractory cases of PN. A systematic review was performed evaluating the use of thalidomide and lenalidomide for PN. Eighteen articles were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
0
21
0
2
Order By: Relevance
“…Recently, the EADV published an expert consensus document on the definition, classification and terminology of chronic prurigo. In most cases, the therapies used to treat PN are relatively ineffective, 8,24 as evidenced in this study by the far higher rates of therapy prescription compared with the respective rates of effectiveness. 2,15,16 In this survey, the primary complaint among all respondents' patients was pruritus, which was also likely responsible for the second most common complaint, sleep disturbance.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Recently, the EADV published an expert consensus document on the definition, classification and terminology of chronic prurigo. In most cases, the therapies used to treat PN are relatively ineffective, 8,24 as evidenced in this study by the far higher rates of therapy prescription compared with the respective rates of effectiveness. 2,15,16 In this survey, the primary complaint among all respondents' patients was pruritus, which was also likely responsible for the second most common complaint, sleep disturbance.…”
Section: Discussionmentioning
confidence: 75%
“…Most of the respondents' patients with PN are prescribed systemic treatments and supportive therapy. In most cases, the therapies used to treat PN are relatively ineffective, 8,24 as evidenced in this study by the far higher rates of therapy prescription compared with the respective rates of effectiveness. An exception would be emollients, which are prescribed in the vast majority of cases and were found to be most effective as supportive agents.…”
Section: Discussionmentioning
confidence: 75%
“…Several studies have shown a rapid decrease in pruritus on thalidomide (50-300 mg/day) (351,352). In a very recent review the authors refer to how patients were started on higher doses of 200 mg or more daily in earlier studies (353). In the majority of studies since then, however, patients received an initial dose ranging from 50 to 200 mg/day, following which the dosage was tailored according to response or the development of side effects.…”
Section: Gabapentin and Pregabalinmentioning
confidence: 99%
“…Thalidomide is teratogenic and there is a dose-related risk of neuropathy, especially in high daily doses (> 100 mg/day) (357). In most cases the peripheral neuropathy is reversible (353). Thalidomide could be considered particularly in a palliative setting (358).…”
Section: Gabapentin and Pregabalinmentioning
confidence: 99%
“…Lenalidomida, é um análogo da talidomida, considerada mais potente e menos neurotóxica. Ambas as medicações já foram utilizadas com sucesso no controle do prurigo (267,268). Há relato isolado que utiliza a imunoglobulina intravenosa no tratamento do PN com sucesso (269).…”
Section: 3 4 -Fisiopatogeniaunclassified